Isolasi dan Identifikasi Bakteri Termofilik Penghasil Enzim Selulase dari Sumber Air Panas Sila - Laury M. Ch. Huwae; Pingkan Aditiawati (ACROPORA: Jurnal Ilmu Kelautan dan Perikanan Papua, 2020)
Cellulose is included in the main polysaccharide group that is widely available in nature. Cellulose is a straight-chain glucose polymer that is bound by β-1,4 glucoside bonds. Cellulase is an enzyme complex consisting of several enzymes that work in stages or together in breaking down cellulose into glucose, by hydrolyzing the β-1,4 glucoside bond in cellulose. Cellulase enzymes have been used in various industries. Industrial applications require enzymes that are stable at high temperatures. Various types of thermostable enzymes can be isolated from thermophilic bacteria, cellulase enzymes are no exception. This study aims to isolate and identify thermophilic bacteria that produce cellulase enzymes from Sila hot springs. The results of isolation and screening of cellulase-producing bacteria from hot water samples obtained by 7 isolates that have the ability to degrade cellulose can produce clear zones on LB-CMC agar selective medium, but CR2 isolates showed the largest zone of 1.5 cm. CR2 isolates were Gram-positive bacteria and were identified as having close relations with Bacillus aryabhattai strain B8W22 using the 16S rRNA method.Keywords: Cellulose; Cellulose enzyme; Thermostable enzyme; Thermophilic bacteria